Manajemen Pelatihan Basic Trauma Cardiac Life Support terhadap Perilaku Perawat dalam Penanganan Kegawatdaruratan - Sartono Sartono; Yayat Suryati; Oyoh Oyoh (Jurnal Keperawatan Silampari, 2022)
This study aims to describe the implementation of basic trauma cardiac life support /BTCLS training and the effect of training management (BTCLS) on the behavior of nurses in handling emergencies in hospitals. Bandung Kiwari. This research method uses quantitative research methods with a quasi-experimental research design. The study results show an overview of the BTCLS training, starting with planning, namely preparation according to SPO. The organizing stage is carried out through communication and technical committee meetings. The implementation phase, beginning with the pretest, continued with material, reflection, skill station, and posttest exams. The control stage involves making activity reports and submitting participant competency certificates. The influence of BTCLS training management on knowledge/cognitive aspects, attitude/affective aspects, and skills/psychomotor aspects on the behavior of nurses in handling emergencies in hospitals. Bandung Kiwari is significant at the significance value of < 0.005. In conclusion, cognitive, affective, and psychomotor BTCLS training gives meaning to the trainees. Keywords: BTCLS, Training Management, Nurse Behavior